Porous carbon material, silicon-carbon composite material and application thereof

By using high-porous porous carbon material as the matrix of silicon-carbon composite material and combining nano-silicon particles, the problem of poor circulation stability of the negative electrode material of lithium-ion battery is solved, and high capacity and excellent circulation performance are achieved.

CN119569029APending Publication Date: 2025-03-07JIANGXI ZICHEN TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411757668.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials, especially silicon-carbon composite materials, have problems such as poor cycle stability and unsatisfactory charge and discharge capacity, which are mainly due to the volume changes of silicon during the embed/delivery process, which lead to unstable electrode surfaces and insufficient electronic and ion conductivity.

Method used

A porous carbon material with high microporosity is used as the matrix of the silicon-carbon composite material. Through the combined activation of CO2 atmosphere and alkali activator, a porous carbon material that meets the specific relationship is prepared, and combined with nano-silicon particles to form an excellent silicon-carbon composite material.

Benefits of technology

The cyclic stability and charge and discharge capacity of silicon-carbon composite materials are improved, the compressive strength of the electrode is enhanced, the particle size and absolute expansion size of the silicon particles are reduced, and the first-time Coulomb efficiency and capacity retention rate of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569029A_ABST
    Figure CN119569029A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a porous carbon material, a silicon-carbon composite material and application of the porous carbon material and the silicon-carbon composite material. According to the porous carbon material, the micropore rate phi, the pore volume Pv and the compressive strength Cs meet the relational expression that (Cs * phi) / Pv is larger than or equal to 550 and smaller than or equal to 1050, and the micropore rate phi gt; and the compressive strength Cs is 600 to 850 MPa. The porous carbon material provided by the invention has high microporosity, and the microporosity phi, the pore volume Pv and the compressive strength Cs of the porous carbon material meet the relation that (Cs.phi) / Pv is more than or equal to 550 and less than or equal to 1050, so that the particle size of silicon particles can be effectively reduced, the absolute expansion of silicon in a carbon matrix is reduced, and the first effect and the cycling stability of the silicon-carbon composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a porous carbon material, a silicon-carbon composite material and applications thereof. Background Art

[0002] At present, the negative electrode materials of lithium-ion batteries used in commercial applications are limited to carbon materials represented by graphite, whose maximum theoretical specific capacity is only 372mAh / g, which can hardly meet the requirements of modern battery applications. Silicon materials are considered to be a promising negative electrode material because of their specific capacity of up to 3579mAh / g, and will gradually replace carbon materials in the negative electrode materials of lithium-ion batteries.

[0003] However, silicon undergoes a volume change of about 300% during the lithium insertion / extraction process, which will cause a series of problems during the cycle. For example, silicon-based negative electrode materials will crack and even pulverize; the volume change prevents the formation of a stable SEI layer on the electrode surface, and the SEI layer repeatedly breaks and forms, consuming a large amount of lithium ions. At the same time, silicon's own low electronic and ionic conductivity limits its output of rate performance.

[0004] The emergence of silicon-carbon composites can solve the above problems to a certain extent. The core of silicon-carbon composites is to store silicon through a porous carbon skeleton and buffer the volume change during the lithium insertion process of silicon through the porous structure of porous carbon. However, the charge and discharge capacity and cycle stability of silicon-carbon composites in the prior art are not ideal.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One object of the present invention is to provide a porous carbon material having high microporosity, and the microporosity φ, pore volume Pv and compressive strength Cs satisfy the relationship 550≤(Cs·φ) / Pv≤1050, and having excellent electrochemical properties.

[0007] Another object of the present invention is to provide a silicon-carbon composite material having excellent charge-discharge capacity and cycle stability.

[0008] Another object of the present invention is to provide a negative electrode sheet.

[0009] Another object of the present invention is to provide a battery.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A porous carbon material, wherein the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 550≤(Cs·φ) / Pv≤1050, wherein the microporosity φ>95%, and the compressive strength Cs is 600-850MPa.

[0012] In some embodiments, the pore volume Pv is 0.7 to 1.2 cm 3 / g.

[0013] In some embodiments, the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 650≤(Cs·φ) / Pv≤1040; wherein the microporosity φ>99%, the compressive strength Cs is 700-850Mpa, and the pore volume Pv is 0.8-1.1cm 3 / g.

[0014] In some embodiments, the specific surface area of ​​the porous carbon material is 1700 to 2800 cm 3 / g.

[0015] A method for preparing the porous carbon material as described above comprises the following steps:

[0016] The carbon source is subjected to a first heat treatment in a CO2 atmosphere to obtain a first carbon material; a mixture of the first carbon material and an alkali activator is subjected to a second heat treatment to obtain a second carbon material; the second carbon material is subjected to a washing treatment and a third heat treatment to obtain the porous carbon material.

[0017] In some embodiments, the flow rate of CO2 is 0.5 to 1.2 L / min.

[0018] In some embodiments, the temperature of the first heat treatment is 850-950° C., and the holding time of the first heat treatment is 9-15 hours.

[0019] In some embodiments, the alkaline activator includes at least one of potassium hydroxide, sodium hydroxide, magnesium hydroxide, and calcium hydroxide.

[0020] In some embodiments, the mass ratio of the first carbon material to the alkali activator is (1.5-6):1.

[0021] In some embodiments, the temperature of the second heat treatment is 700-850° C., and the holding time of the second heat treatment is 1-3 hours.

[0022] In some embodiments, the temperature of the third heat treatment is 850-950° C., and the holding time of the third heat treatment is 2-5 hours.

[0023] In some embodiments, the washing treatment includes acid washing and water washing.

[0024] A silicon-carbon composite material comprises the porous carbon material or the porous carbon material obtained by the method, and nano silicon particles located in the pores of the porous carbon material.

[0025] In some embodiments, in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the ratio of the intensity value of the lithium insertion peak at 0.30-0.45V to the strongest peak value within 0-0.25V is less than 0.05.

[0026] In some embodiments, the mass content of the nano silicon particles in the silicon-carbon composite material is 45% to 65%.

[0027] In some embodiments, the surface of the silicon-carbon composite material further includes a coating layer, and the coating layer contains at least one of a fast ion conductor, amorphous carbon, and a high molecular polymer.

[0028] In some embodiments, the compressive strength of the silicon-carbon composite material is 820-1100 MPa.

[0029] In some embodiments, in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the number of lithium insertion peaks at 0.30-0.45V is 0.

[0030] A negative electrode sheet comprises the silicon-carbon composite material.

[0031] A battery comprises the negative electrode sheet.

[0032] An electrical device comprises the battery.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The porous carbon material of the present invention has a high microporosity, and the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship 550≤(Cs·φ) / Pv≤1050. The high microporosity (microporosity φ>95%) porous carbon can effectively reduce the particle size of silicon particles in the silicon-carbon composite material, reduce the absolute expansion size of silicon inside the carbon matrix, and improve the electrode cycle stability; the high microporosity porous carbon can effectively improve the compressive strength of the porous carbon matrix, which is beneficial to reduce the occurrence of cracking of the silicon-carbon composite material after rolling during the preparation of the electrode, inhibit the generation of silicon oxides inside the particles, and thus improve the first coulombic efficiency.

[0035] (2) The silicon-carbon composite material of the present invention has a suitable silicon content, high compressive strength, high charge and discharge capacity, and good cycle stability.

[0036] (3) The battery of the present invention has the characteristics of high initial efficiency and high capacity retention rate. The capacity of the battery after 100 cycles is above 1720 mAh / g, and the capacity retention rate after 100 cycles is 90% or above. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 is a pore size distribution diagram of the porous carbon material in Example 1 of the present invention;

[0039] Figure 2 is a compressive strength curve of the porous carbon material in Example 1 of the present invention;

[0040] Figure 3 is a compressive strength curve of the silicon-carbon composite material in Example 1 of the present invention;

[0041] Figure 4 dQ / dV curve of a battery prepared from the silicon-carbon composite material in Example 1 of the present invention;

[0042] Figure 5 This is a dQ / dV curve of a battery prepared from the silicon-carbon composite material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0044] According to one aspect of the present invention, the present invention relates to a porous carbon material, the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 550≤(Cs·φ) / Pv≤1050, wherein the microporosity φ>95%, and the compressive strength Cs is 600~850MPa.

[0045] The porous carbon material of the present invention has a high microporosity (according to the definition of the International Association of Pure and Applied Chemistry (IUPAC), micropores refer to pores with a pore size less than 2nm), and the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the above relationship, are not subject to theoretical constraints, and can effectively reduce the particle size of silicon particles, reduce the absolute expansion size of silicon inside the carbon matrix, and improve the cycle stability of the electrode; high microporous porous carbon can effectively improve the compressive strength of the porous carbon matrix, which is beneficial to reduce the occurrence of cracking of silicon-carbon composite materials after rolling during the preparation of pole pieces, inhibit the generation of silicon oxides inside the particles, and thus improve the first coulomb efficiency. In some embodiments, the value of φ is, for example, 95.1%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or 100%, or any range between the two. In some embodiments, the value of (Cs·φ) / Pv is 550, 560, 570, 580, 600, 620, 650, 680, 700, 750, 780, 800, 820, 850, 880, 900, 950, 980, 1000 or 1050, or any range between two values.

[0046] In some embodiments, the pore volume Pv of the porous carbon material of the present invention is 0.7 to 1.2 cm 3 / g, for example 0.7cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 1cm 3 / g, 1.05cm 3 / g, 1.1cm 3 / g, 1.15cm 3 / g or 1.2cm 3 / g, etc., or any range between the two. Not subject to theoretical constraints, the microporosity of porous carbon materials is positively correlated with their compressive strength (that is, the higher the microporosity, the greater the compressive strength); under the same microporosity, the pore volume is negatively correlated with the compressive strength. High pore volume porous carbon can increase the silicon content inside the silicon-carbon composite material particles, effectively improving the charge and discharge capacity. The applicant of the present invention has found that when the pore volume is increased to a certain value, pore expansion will occur when the pore volume continues to increase, that is, the pore diameter increases and the microporosity decreases. The porous carbon material of the present invention has a suitable pore volume. When the porous carbon pore volume is small, it is difficult to infiltrate an appropriate amount of silicon, and the silicon-carbon composite material has a small silicon content, resulting in a low reversible capacity; when the porous carbon pore volume is large, due to the phenomenon of pore expansion during the preparation process, its micropores are low (φ<95%), which in turn causes its compressive strength to decrease.

[0047] In some embodiments, the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 650≤(Cs·φ) / Pv≤1040; wherein the microporosity φ>99%, the compressive strength Cs is 700-850 MPa, and the pore volume Pv is 0.8-1.1 cm 3 / g.

[0048] In some embodiments, the porous carbon material of the present invention has a suitable surface area, with a specific surface area of ​​1700 to 2800 cm 3 / g, including but not limited to 1700cm 3 / g、1800cm 3 / g、1900cm 3 / g、2000cm 3 / g、2100cm 3 / g、2500cm 3 / g、2600cm 3 / g、2800cm 3 / g, etc., or any range between the two.

[0049] According to another aspect of the present invention, the present invention also relates to a method for preparing the porous carbon material, comprising the following steps:

[0050] The carbon source is subjected to a first heat treatment in a CO2 atmosphere to obtain a first carbon material; a mixture of the first carbon material and an alkali activator is subjected to a second heat treatment to obtain a second carbon material; the second carbon material is subjected to a washing treatment and a third heat treatment to obtain the porous carbon material.

[0051] The method for preparing the porous carbon material of the present invention obtains a porous carbon material with high microporosity through the combined activation of CO2 gas and an alkaline activator, which can effectively reduce the usage of chemically activated KOH, slow down the corrosion rate of the equipment, and reduce the activation cost at the same time; the high microporosity porous carbon can effectively improve the compressive strength of the porous carbon matrix, which is beneficial to reduce the occurrence of cracks in the silicon-carbon composite material after rolling during the preparation of the electrode, inhibit the generation of silicon oxides inside the particles, and thus improve the first coulomb efficiency.

[0052] In some embodiments, the carbon source includes at least one of a high molecular weight polymer, petroleum coke, and pitch coke.

[0053] In some embodiments, the flow rate of CO2 is 0.5-1.2 L / min, including but not limited to 0.5 L / min, 0.8 L / min, 1 L / min, 1.1 L / min, 1.2 L / min, etc., or any range between the two. The CO2 adopts an appropriate flow rate to ensure a better activation effect.

[0054] In some embodiments, the temperature of the first heat treatment is 850-950°C, such as 850°C, 860°C, 870°C, 900°C, 920°C, 930°C, 950°C, etc., or any range between the two. The holding time of the first heat treatment is 9-15h, such as 9h, 10h, 11h, 12h, 13h, 15h, etc., or any range between the two. The present invention adopts suitable first heat treatment conditions to ensure the CO2 activation effect. In some embodiments, the first carbon material is subjected to natural cooling treatment.

[0055] In some embodiments, the alkaline activator includes at least one of potassium hydroxide, sodium hydroxide, magnesium hydroxide and calcium hydroxide. In some embodiments, the mass ratio of the first carbon material to the alkaline activator is (1.5-6):1, such as 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 5:1 or 6:1, or any range value therebetween. The first carbon material and the alkaline activator use an appropriate mass ratio to ensure the activation effect.

[0056] In some embodiments, the temperature of the second heat treatment is 700-850°C, such as 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, etc., or any range between the two. The holding time of the second heat treatment is 1-3h, such as 1h, 1.5h, 2h, 2.5h or 3h, etc., or any range between the two. The present invention adopts suitable second heat treatment conditions to ensure the activation effect of the alkali activator. In some embodiments, the second heat treatment is carried out under protective gas conditions, such as nitrogen, inert gas, and the flow rate of the protective gas is 0.5-5L / min. In some embodiments, the second carbon material is subjected to natural cooling treatment.

[0057] In some embodiments, the temperature of the third heat treatment is 850-950°C, such as 850°C, 880°C, 900°C, 920°C, 950°C, etc., or any range between the two. The holding time of the third heat treatment is 2-5h, such as 2h, 2.5h, 3h, 4h or 5h, etc., or any range between the two. The present invention adopts suitable third heat treatment conditions to obtain a porous carbon material with high microporosity, suitable pore volume and compressive strength.

[0058] In some embodiments, the washing treatment includes acid washing and water washing. The acid washing uses 0.5-2 mol / L hydrochloric acid. The water washing includes repeated washing with deionized water until the filtrate is neutral.

[0059] According to another aspect of the present invention, the present invention also relates to a silicon-carbon composite material, comprising a porous carbon material or a porous carbon material obtained by the method described, and nano-silicon particles located in the pores of the porous carbon material.

[0060] The silicon-carbon composite material of the present invention and the porous carbon material of the present invention have high microporosity (according to the definition of the International Association of Pure and Applied Chemistry (IUPAC), micropores refer to pores with a pore size less than 2 nm), and the microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the above relationship, are not subject to theoretical constraints, can effectively reduce the particle size of silicon particles, reduce the absolute expansion size of silicon inside the carbon matrix, and improve the electrode cycle stability; high-micropore porous carbon can effectively improve the compressive strength of the porous carbon matrix, which is beneficial to reduce the occurrence of cracking of the silicon-carbon composite material after rolling during the preparation of the electrode piece, inhibit the generation of silicon oxides inside the particles, thereby improving the first coulomb efficiency, and having excellent electrochemical performance.

[0061] In some embodiments, in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the ratio of the intensity value of the lithium insertion peak at 0.30-0.45V to the strongest peak value in the range of 0-0.25V is less than 0.05. Without being bound by theory, in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the peak in the range of 0-0.25V corresponds to the lithium insertion peak of silicon, and the lithium insertion peak of 0.30-0.45V corresponds to the lithium insertion peak of SiO x The silicon-carbon composite material of the present invention has a high compressive strength. x The intensity of the lithium insertion peak of the silicon is much smaller than that of the lithium insertion peak of the silicon, which indicates that there is basically no particle breakage in the electrode during the rolling process, which greatly reduces and avoids the SiO generated by the reaction of elemental silicon in the silicon-carbon composite material particles and air. x Resulting in a decrease in capacity and initial efficiency.

[0062] In some embodiments, in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the number of lithium insertion peaks at 0.30-0.45V is 0, that is, the first-order derivative of the lithium insertion dQ / dV curve at 0.30-0.45V does not have a zero value (and the left and right sides have opposite signs). Without being bound by theory, in some embodiments, it can be found in the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material of the present invention that no SiO x The lithium insertion peak of the present invention is 0.30-0.45V, which is due to the high compressive strength of the silicon-carbon composite material. The electrode is basically free of particle breakage during the rolling process, which avoids the reaction of SiO2 generated by the reaction of elemental silicon in the silicon-carbon composite material particles and air. x Resulting in a decrease in capacity and initial efficiency.

[0063] In some embodiments, the silicon-carbon composite material of the present invention has a suitable silicon content, and the mass content of nano-silicon particles in the silicon-carbon composite material is 45% to 65%, for example, 45%, 48%, 50%, 52%, 55%, 60% or 65%, or any range value between the two.

[0064] In some embodiments, the surface of the silicon-carbon composite material further includes a coating layer, and the coating layer includes at least one of a fast ion conductor, amorphous carbon and a high molecular polymer. By providing the coating layer, the electrochemical performance of the silicon-carbon composite material can be further improved.

[0065] In some embodiments, the silicon-carbon composite material of the present invention has a high compressive strength of 820 to 1100 MPa, for example, 830 MPa, 850 MPa, 900 MPa, 950 MPa, 1000 MPa, 1050 MPa, 1060 MPa, 1080 MPa, 1100 MPa, etc., or any range value between two thereof.

[0066] According to another aspect of the present invention, the present invention relates to a method for preparing a silicon-carbon negative electrode material, comprising the following steps: vapor depositing a porous carbon material in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.

[0067] In some embodiments, the silicon source comprises a conventional siliconizing gas, and includes but is not limited to at least one of monosilane (SiH4), disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives.

[0068] In some embodiments, the temperature of vapor deposition is 400-550°C, for example, but not limited to, 400°C, 450°C, 480°C, 500°C, 510°C, 550°C, etc., or any range between the two.

[0069] In some embodiments, the preparation method of the silicon-carbon composite material includes: placing the porous carbon material in a heat treatment device, evacuating the device at room temperature and introducing a protective gas to replace the air with the protective gas. In the protective gas atmosphere, the temperature is raised to 400-550° C. at 2-8° C. / min, and a silicon source is introduced at a flow rate of 0.5-1.5 L / min, and the introduction of the silicon source is stopped after the temperature is kept for 2-3.5 hours.

[0070] In some embodiments, the method further includes: coating the silicon-carbon negative electrode material to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer comprises at least one of amorphous carbon, a fast ion conductor and a high molecular polymer. The coating treatment specifically includes: performing a third heat treatment after vapor deposition while continuously introducing a coating source gas. The present invention further coats the surface of the silicon-carbon negative electrode material to improve the comprehensive performance of the final silicon-carbon negative electrode material.

[0071] In some embodiments, after the porous carbon material is vapor deposited in an atmosphere containing a silicon source, the temperature is raised to 600-700°C at a rate of 2-8°C / min, and a coating gas source is introduced at a flow rate of 0.1-0.5L / min. The introduction of the coating gas source is stopped after keeping the temperature for 1-3 hours.

[0072] In some embodiments, the protective gas includes nitrogen, an inert gas such as helium, and the like.

[0073] In some embodiments, the coating source gas source includes acetylene, methane, ethane, isopropane, propane, butane, isobutane, ethylene, butene, propylene, acetylene (C2H2), vinyl chloride, ethyl chloride, vinyl fluoride, pentachlorofluoroethane, difluoroethane, 1,1-difluoroethylene, fluoromethane, chloromethane, difluoromethane, trifluoromethane, etc.

[0074] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet comprising the above-mentioned silicon-carbon composite material.

[0075] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer located on at least one side of the surface of the negative electrode current collector, and the negative electrode material layer contains the above-mentioned silicon-carbon composite material.

[0076] According to another aspect of the present invention, the present invention also relates to a battery comprising the above-mentioned negative electrode sheet.

[0077] The battery of the present invention has high capacity and excellent cycle performance. In some embodiments, the battery comprises the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.

[0078] According to another aspect of the present invention, the present invention also relates to an electrical device, comprising the above-mentioned battery. The electrical device may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like.

[0079] The following is further explained in conjunction with specific embodiments and comparative examples.

[0080] Example 1

[0081] A method for preparing a porous carbon material comprises the following steps:

[0082] Take 1kg of resin and place it in a rotary kiln, and pass CO2 at a rate of 1L / min. Heat the rotary kiln to 900℃ at a rate of 5℃ / min for the first heat treatment, and keep it warm for 12h. After the rotary kiln is cooled naturally, take out the material for standby. Take 500g of porous carbon obtained after the initial activation and 200g of KOH and place them in a rotary kiln, and pass N2 at a rate of 1L / min. Heat the rotary kiln to 800℃ at a rate of 5℃ / min for the second heat treatment, and keep it warm for 1.5h. After the rotary kiln is cooled naturally, take out the material and place it in a 1mol / L HCl solution, stir, filter and wash. After washing with hydrochloric acid, wash repeatedly with deionized water until the filtrate is neutral. After drying, place the intermediate product in a rotary kiln in a nitrogen atmosphere at 900℃ for the third heat treatment, and keep it warm for 3h to obtain the final high pore volume and high microporosity porous carbon material.

[0083] A method for preparing a silicon-carbon composite material comprises the following steps:

[0084] Take the above 1kg porous carbon of this embodiment and place it in a rotary kiln, evacuate at room temperature and introduce N2 to replace the air with N2. Under the protection of nitrogen atmosphere, heat up to 450℃ at 5℃ / min, and introduce SiH4 at a flow rate of 0.8L / min. After keeping warm for 3h, close the SiH4 valve. Then heat up to 650℃ at 5℃ / min, and introduce C2H2 at a flow rate of 0.2L / min. After keeping warm for 2h, close the C2H2 valve to obtain a silicon-carbon negative electrode material with a silicon content of 60% by mass.

[0085] Example 2

[0086] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0087] The flow rate of CO2 gas is 0.5 L / min.

[0088] The method for preparing the silicon-carbon composite material in this embodiment is the same as that in Example 1 except that the porous carbon material in this embodiment is used.

[0089] Example 3

[0090] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0091] The amount of KOH used was 100 g.

[0092] The method for preparing the silicon-carbon composite material in this embodiment is the same as that in Example 1 except that the porous carbon material in this embodiment is used.

[0093] Example 4

[0094] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0095] The amount of KOH used was 300 g.

[0096] The method for preparing the silicon-carbon composite material in this embodiment is the same as that in Example 1 except that the porous carbon material in this embodiment is used.

[0097] Example 5

[0098] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0099] The amount of KOH used was 160 g.

[0100] The method for preparing the silicon-carbon composite material in this embodiment is the same as that in Example 1 except that the porous carbon material in this embodiment is used.

[0101] Comparative Example 1

[0102] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0103] No CO2 was used for activation, and the amount of KOH used was adjusted to 280 g.

[0104] The preparation method of the silicon-carbon composite material in this comparative example is different from that in Example 1 in that: the porous carbon material in this comparative example is used, and the deposition time of SiH4 at 450° C. is extended from 3 h to 3.5 h.

[0105] Comparative Example 2

[0106] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0107] No KOH was used for activation, and the CO2 gas flow rate was adjusted to 1.9 L / min.

[0108] The preparation method of the silicon-carbon composite material in this comparative example is different from that in Example 1 in that: the porous carbon material in this comparative example is used, and the deposition time of SiH4 at 450° C. is extended from 3 h to 4 h.

[0109] Comparative Example 3

[0110] A method for preparing a porous carbon material, which differs from Example 1 in that:

[0111] The flow rate of CO2 gas was 1.5 L / min.

[0112] The method for preparing the silicon-carbon composite material in this embodiment is the same as that in Example 1 except that the porous carbon material in this embodiment is used.

[0113] Experimental example

[0114] 1. Performance test of porous carbon materials

[0115] The porous carbon materials in each embodiment and comparative example were tested for specific surface area, pore volume, microporosity and compressive strength. The testing method is as follows:

[0116] Microporosity test method: The NLDFT model is used to fit the nitrogen isothermal adsorption-desorption curve to obtain the pore size distribution of porous carbon, where the proportion of pore volume with a pore size of 2 nm or less to the total pore volume is the microporosity.

[0117] Compressive strength test method: Use a micro compression tester with a flat pressure head of 50μm in diameter. Clamp the sample between two indicators and measure the sample in increments of 0.1μm until it increases to 200μm. Measure the pressure and deformation during the deformation of the sample. The horizontal axis of the obtained data graph is the compression displacement, and the vertical axis is the pressure calculated by the instrument. The pressure corresponding to the inflection point of the curve is the compressive strength of the material.

[0118] The specific surface area and pore volume were determined by nitrogen isothermal adsorption-desorption method.

[0119] The performance test results of the porous carbon materials of various embodiments and comparative examples are shown in Table 1. The pore size distribution diagram of the porous carbon material in Example 1 is shown in Table 1. Figure 1 The compressive strength curve of the porous carbon material in Example 1 is shown in Figure 2 The compressive strength curve of the silicon-carbon composite material in Example 1 is shown in Figure 3 shown.

[0120] Table 1 Performance test results of porous carbon materials

[0121]

[0122] It can be seen from Table 1 that the microporosity of the porous carbon material is positively correlated with its compressive strength, that is, the higher the microporosity, the greater the compressive strength; under the condition of the same microporosity, the pore volume is negatively correlated with the compressive strength. In addition, combining CO2 gas activation with alkali activation is beneficial to the preparation of porous carbon materials with suitable pore volume and high micropores. When the pore volume is increased to a certain value, the pore expansion phenomenon will occur when the pore volume continues to increase, that is, the pore diameter increases and the microporosity decreases. The microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon materials obtained in each embodiment of the present invention satisfy the relationship 550≤(Cs·φ) / Pv≤1050. The compressive strength of the porous carbon materials obtained in Comparative Examples 1 to 3 is too low, and the value of (Cs·φ) / Pv is too low.

[0123] 2. Performance test of silicon-carbon negative electrode materials

[0124] The silicon-carbon negative electrode materials obtained in each embodiment and comparative example were tested for compressive strength and silicon content.

[0125] The compressive strength test method of the silicon-carbon negative electrode material refers to the test method of the porous carbon material mentioned above.

[0126] Test of silicon content: The test is carried out by thermogravimetry. In air atmosphere, a sample of a certain mass m1 is heated to 600℃ at room temperature, kept warm for 1 hour, and then continued to be heated to 1000℃, kept warm for 1 hour. After natural cooling, the mass of the sample m2 is weighed. The silicon content is 0.467×m2 / m1.

[0127] The performance test results of the silicon-carbon negative electrode materials of various embodiments and comparative examples are shown in Table 2.

[0128] Table 2 Performance test results of silicon-carbon negative electrode materials

[0129] Group Compressive strength(Mpa) Silicon content (wt%) Example 1 965 60 Example 2 1051 45 Example 3 983 49 Example 4 830 56 Example 5 953 54 Comparative Example 1 741 60 Comparative Example 2 449 60 Comparative Example 3 618 52

[0130] It can be seen from Table 2 that, under the same pore volume and deposition process, the greater the microporosity, the higher the silicon content, because the micropores have a stronger adsorption force for gas molecules. The methods of various embodiments of the present invention can obtain silicon-carbon negative electrode materials with high compressive strength and high silicon content.

[0131] 3. Battery performance test

[0132] The silicon-carbon composite materials of each embodiment and comparative example were made into half-cells, and the electrochemical performance was tested. The preparation method of the half-cell specifically includes: mixing the silicon-carbon composite material with the binder polyacrylic acid (PAA) and the conductive carbon black (SP) in a mass ratio of 70:20:10, preparing the mixture into a slurry with deionized water, evenly coating it on a copper foil, vacuum drying at 80°C for 24 hours, and rolling to obtain a half-cell electrode, wherein the electrode compaction density is about 1.0g / cm 3 , surface density is about 2.5mg / cm 2 Then, the lithium sheet was used as the counter electrode, and 1 mol / L LiPF6 was dissolved in a four-component mixed solvent as the electrolyte, wherein the volume ratio of ethylene carbonate (EC): dimethyl carbonate (DMC): vinylene carbonate (VC): fluoroethylene carbonate (FEC) in the four-component solvent was 1:1:1:1, and a polypropylene microporous membrane was used as the separator to assemble a CR2032 button half-cell in a vacuum glove box.

[0133] Electrochemical performance test conditions: stand for 10 minutes, discharge at a constant current of 0.1C to 5mV, stand for 5 minutes, discharge at a constant current of 0.02C to 5mV, stand for 5 minutes, discharge at a constant current of 0.01C to 5mV; stand for 10 minutes, charge at a constant current of 0.1C to 2.0V. Cycle 100 times.

[0134] The performance test results of the batteries of various embodiments and comparative examples are shown in Table 3. The dQ / dV curve of the battery prepared from the silicon-carbon composite material in Example 1 is shown in Table 3. Figure 4 The dQ / dV curve of the battery prepared from the silicon-carbon composite material in Comparative Example 1 is shown in Figure 5 shown.

[0135] Table 3 Battery performance test results

[0136]

[0137] In Table 3, I SiOx / I Si The dQ / dV curve of the first lithium insertion shows the intensity value (I SiOx ) and the strongest peak value (I Si ) ratio.

[0138] It can be seen from Table 3 that the battery prepared with the silicon-carbon negative electrode material obtained by the method of the present invention has a high first lithium desorption capacity, coulombic efficiency, and good cycle performance. The first lithium desorption capacity can reach 2434 mAh / g, the coulombic efficiency can reach 93.2%, the capacity after 100 cycles is 1728 mAh / g or above, and the capacity retention rate after 100 cycles is above 90%.

[0139] By comparing Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that under the condition of the same silicon content, the capacity and efficiency of the silicon-carbon negative electrode material are positively correlated with the microporosity of its porous carbon matrix. Figure 4 It can be found in the dQ / dV curve of the first lithium insertion that no SiO x The lithium insertion peak of Example 2-5 is not found in the dQ / dV curve of the first lithium insertion at 0.30-0.45V. x The lithium insertion peak, or even if there is a lithium insertion peak, its intensity value (I SiOx ) and the strongest peak value (I Si ) is also less than 0.05; Figure 5 It can be found in the dQ / dV curve of the first lithium insertion that SiO x The lithium insertion peak is 0.5 of the intensity of the strongest peak in the range of 0 to 0.25 V. This is because the compressive strength of the silicon-carbon particles is low, and the particles of the pole piece are broken during the rolling process, causing the silicon in the silicon-carbon particles to react with air to form silicon oxide, resulting in a decrease in capacity and initial efficiency.

[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A porous carbon material, characterized in that: The microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 550≤(Cs·φ) / Pv≤1050, wherein the microporosity φ>95%, and the compressive strength Cs is 600-850 MPa.

2. The porous carbon material according to claim 1, characterized in that The pore volume Pv is 0.7 to 1.2 cm 3 / g.

3. The porous carbon material according to claim 2, characterized in that: The microporosity φ, pore volume Pv and compressive strength Cs of the porous carbon material satisfy the relationship: 650≤(Cs·φ) / Pv≤1040; wherein the microporosity φ>99%, the compressive strength Cs is 700-850 MPa, and the pore volume Pv is 0.8-1.1 cm 3 / g.

4. The porous carbon material according to claim 1, characterized in that The specific surface area of ​​the porous carbon material is 1700 to 2800 cm 3 / g.

5. A silicon-carbon composite material, characterized in that: The porous carbon material comprises the porous carbon material according to any one of claims 1 to 4 and nano-silicon particles located in the pores of the porous carbon material.

6. The silicon-carbon composite material according to claim 5, characterized in that: Contains at least one of the following features (1) to (4): (1) In the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the ratio of the intensity value of the lithium insertion peak at 0.30-0.45V to the strongest peak value within 0-0.25V is less than 0.05; (2) The mass content of nano silicon particles in the silicon-carbon composite material is 45% to 65%; (3) The surface of the silicon-carbon composite material further includes a coating layer, wherein the coating layer comprises at least one of a fast ion conductor, amorphous carbon and a high molecular polymer; (4) The compressive strength of the silicon-carbon composite material is 820 to 1100 MPa.

7. The silicon-carbon composite material according to claim 6, characterized in that: In the dQ / dV curve of the first lithium insertion of the silicon-carbon composite material, the number of lithium insertion peaks at 0.30-0.45V is 0.

8. A negative electrode sheet, characterized in that: A silicon-carbon composite material comprising any one of claims 5 to 7.

9. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Cited By

  • Negative electrode material, negative electrode plate and secondary battery

    CN121617931A

  • Silicon-carbon composite material and application thereof

    CN122370374A

  • Porous carbon material, silicon-carbon composite material, and use thereof

    WO2026119038A1